Penerapan Metode Permainan melalui Layanan Bimbingan Klasikal untuk Meningkatkan Keterampilan Manajemen Waktu Peserta Didik Kelas XI di SMAN 1 Kediri - Miftah Nur Salima; Isfauzi Hadi Nugroho; Lely Yuanita Permata Sari (CV. ITTC INDONESIA, 2025)
This study aims to improve time management skills among 11th-grade students at SMAN 1 Kediri through the use of game-based methods in classroom guidance services. The research employed Guidance and Counseling Action Research (PTBK) conducted in two cycles, involving 31 students from class XI-K as subjects. Data were collected using time management questionnaires and observations, and the data analyzed using descriptive quantitative techniques. In the first cycle, 32% of students were categorized as high, 55% as moderate, and 13% as low in time management skills. After service improvements in the second cycle, the percentage of students in the low category decreased to 0%, while the moderate category increased to 58%. These results indicate an improvement in students’ time management skills. Based on the findings of the research, it can be concluded that the game-based method has proven effective in creating an enjoyable guidance atmosphere and encouraging active student participation in better understanding and managing their time.